Investigation of (CH3OH)-C-13 methanol: new laser lines and assignments - Moraes, João Carlos Silos [UNESP]; Pizoletto, O. P.; Scalabrin, A.; Allen, M. D.; Evenson, K. M. (Springer, 2001)
We have reinvestigated (CH3OH)-C-13 as a source of far-infrared (FIR) laser emission using a CO2 laser as a pumping source. Thirty new FIR laser lines in the range 36.5 mum to 202.6 mum were observed and characterized. Five of them have wavelengths between 36.5 and 75 mum and have sufficient intensity to be used in LMR spectroscopy. Using Fourier-transform spectroscopic data in the infrared (IR) and FIR regions we have determined the assignment for 10 FIR laser transitions and predict nine frequencies for laser lines which have yet to be observed.